ZnO nanoflower-based photoelectrochemical DNAzyme sensor for the detection of Pb2+ - Zhang, Bintian; Lu, Lili; Hu, Qichang; Huang, Feng; Lin, Zhang (Biosensors & bioelectronics, 2014)
Lead contamination is now widespread, and exposure to lead may cause adverse effects on human beings. In this study, a photoelectrochemical sensor based on flower-like ZnO nanostructures was developed for Pb(2+) detection, using a Pb(2+)-dependent DNAzyme as the recognition unit and a double-strand DNA intercalator, Ru(bpy)2(dppz)(2+) (bpy=2,2'-bipyridine, dppz=dipyrido[3,2-a:2',3'-c] phenazine) as the photoelectrochemical signal reporter. The ZnO nanoflower was fabricated on an indium tin oxide (ITO) electrode by the convenient hydrothermal decomposition method. The morphology and photoelectrochemical property of the ZnO nanoflowers were characterized by SEM, XRD and photocurrent measurements. DNAzyme-substrate duplex was assembled on an ITO/ZnO electrode through electrostatic adsorption. In the presence of Pb(2+), RNA-cleavage activity of the DNAzyme was activated and its substrate strand was cleaved, resulting in the release of Ru(bpy)2(dppz)(2+) from the DNA film and the concomitant photocurrent decrease. The detection principle was verified by fluorescence measurements. Under the optimized conditions, a linear relationship between photocurrent and Pb(2+) concentration was obtained over the range of 0.5-20 nM, with a detection limit of 0.1 nM. Interference from other common metal ions was found negligible. Applicability of the sensor was demonstrated by analyzing lead level in human serum and Pb(2+) spiked water samples. This facile and economical sensor system showed high sensitivity and selectivity, thus can be potentially applied for on-site monitoring of lead contaminant.
Keywords: Electrochemical Techniques; nanostruktury; Equipment Design; Intercalating Agents; olovo; chemické látky znečišťující vodu; jezera; pitná voda; Water Pollutants, Chemical; oxid zinečnatý; ZnO nanoflower; Biosensing Techniques; Zinc Oxide; interkalátory; Lead; limita detekce; Lead contamination; Drinking Water; Photoelectrochemical sensor; elektrochemické techniky; biosenzitivní techniky; DNAzyme; Limit of Detection; DNA katalytická; Lakes; Nanostructures; design vybavení; DNA, Catalytic